Recent trends in the number of hunters and the harvest of wildfowl in the Camargue, France: preliminary results - Mondain-Monval, Jean-Yves; Olivier, Anthony; Le Bihan, Aubin (Wildfowl, 2013)
In 1999, the Office National de la Chasse et de la Faune Sauvage (ONCFS) made a detailed survey of hunting activity in the Camargue, southern France. A full inventory of the Camargue shooting estates was recorded and a questionnaire on hunting practices was completed for each of these estates. The number of hunters on communal and company estates has declined considerably in recent years, whereas the number of hunters on private estates has remained stable. Between 1999 and 2008, managers from 105 of the private shooting estates voluntarily sent the estates’ bag statistics to ONCFS, with 35 of these private estates additionally providing data from 1992 onwards. Trends in the bag records for different duck species on the 35 estates with longer-term data are compared with the recent trends in wintering numbers for the same species in the West Mediterranean region. A simple bag return form has been given to 2,000 hunters on communal and company shooting estates since 2004. The voluntary return of these forms to ONCFS is still rather low with c. 5% returned in 2008–2009, but is steadily increasing.